A nalyse the fluctuation and water level trend in Saigon - Dong Nai river system - Viet, Luong Van; Luan, Pham Dang Manh Hong; Tuan, Le Anh (VNU Journal of Science: Earth and Environmental Sciences; Vol 25 No 4, 2009)
Abstract